دراسة تأثير السيلينيوم في تقليل الأثر السمي للمنغنيز عند الهامستر السوري (Journal of Hama University, 2024)
ABSTRACTThis research was conducted to study the physiological changes resulting from excessive exposure to manganese by knowing some variables of some liver functions (aspartate aminotransferase and alanine aminotransferase) and knowing the role of selenium in reducing the toxic effect of manganese on the liver and improving these physiological variables, all of this experimentally in Syrian hamsters. .The experiment included (30) hamsters. The animals were distributed randomly into three groups. Each group included 10 experimental animals with similar weights according to the following:-The first group (G1): The natural control group. The animals of this group were dosed with physiological saline solution, NaCl, at a concentration of 0.9%. They were given the normal diet, and were returned as a negative control group.-The second group (G2): The animals of this group were given manganese chloride at a concentration of 100 mg/kg of body weight via oral dosage using a special syringe for this purpose daily for a period of four weeks, and they were returned as a positive control group.-The third group (G3): The animals of this group were given manganese chloride at a concentration of 100 mg/kg of body weight via oral dosage using a special syringe for this purpose. They were also given sodium selenate with the diet at a concentration of 1 mg/kg of diet daily for a period of four weeks.-All blood samples were obtained at the end of the fourth week of the experiment directly from the heart.-The results showed: physiological changes in liver function resulting from manganese poisoning, represented by a significant increase (P≤0.05) in the average and concentration of aspartate aminotransferase and alanine aminotransferase in the second group treated with manganese chloride (G2), when compared with the normal control group (G1). There was a significant decrease (P≤0.05) in the concentration of aspartate aminotransferase and alanine aminotransferase in the third group (G3) treated with manganese chloride and treated with sodium selenite when compared with the positive control group (G2).
Keywords: : manganese poisoning, sodium selenite, selenium poisoning, thyroid-stimulating hormone, aspartate aminotransferase, Syrian hamster.; manganese poisoning, sodium selenite, selenium poisoning, aspartate aminotransferase, Syrian hamster.